Knowledge domain, research hotspots and frontiers in physiology teaching reforms from 2012 to 2021: A bibliometric and knowledge-map analysis - Xu, Jia; Sun, Shimeng; Zhao, Yadong; Ma, Qing (Frontiers in Medicine, 2023)
Objective: To identify author collaborations and impact; participating countries, institutions, and journals; evaluate the knowledge base; and analyze research hotspots and frontiers in teaching reforms in physiology. Methods: Articles and reviews related to teaching reforms in physiology published between January 1, 2012, and December 31, 2021, were obtained from the Web of Science Core Collection. Two Scientometric software applications (CiteSpace 5.7 and VOSviewer 1.6.15) were used to perform bibliometric and knowledge-map analysis, generate network maps, and identify research trends and top keywords, authors, co-cited authors, institutions, countries, journals, and references. Results: The search identified a total of 2882 papers in 466 academic journals by 13895 authors from 4072 organizations in 67 countries/regions. Physiology teaching reform-related publications increased rapidly over time. Arango-Lasprilla and Rivera published the most papers, while Moseley had the most co-citations. Active collaborations among physiology researchers were noted. Advances in Physiology Education published the most papers on physiology teaching reforms and was also the top co-cited journal in the Medicine/Medical/Clinical, Psychology/Education/Health, and Neurology/Sports/Ophthalmology fields. The United States and University of California published the most physiology teaching publications in the search criteria. Ten references (research articles and reviews) on mechanisms and diseases were identified as the knowledge base. The mainstream research directions were education, Alzheimer’s disease, performance, physiology, and risk factors. Mental health and emotion regulation are increasing in significance and may become new hotspots. The research trend to move from the field of pain pathogenesis to the field of neuropsychiatry has become increasingly clear. This tendency away from peripheral system-based disorders to central system-based orders is inextricably linked to further developments in physiological understanding of the brain. Conclusion: This study analyzed the research hot spots and frontiers of teaching reforms on in physiology using bibliometric and visual methods. Based on the results, rehabilitation, neurosciences, and infectious disease are hot topics in physiology. In particular, the pathogenesis of neurological diseases, treatment strategies, and technology updates have gradually become research hotspots. We predict that this trend is closely related to the implementation of brain research programs in various countries. These findings provide helpful references for scholars focusing on physiology education.